Investigation of the Relationship between Underground Economy and Social Development in a Selection of Middle East Countries - seyed javad aghajeri; mansour zaranezhad; Mohammad hadi Akbarzadeh (توسعه اجتماعی, 2019)
Underground economy with its complex, diverse and widespread aspects leads to various economic and social issues, obscure data and statistics, inadequate performance of socio-economic policies, and finally, the slowdown of the development process in different societies. Studies conducted about the underground economy have mainly focused on estimating the size of the underground economy or the effects of this phenomenon on macroeconomic variables. Given the impartible linkage of underground economy with social and cultural issues, the consequences of underground economy on society and social development have been less addressed. Therefore, the main objective of the current study was to investigate the effect of underground economy on social development in selected countries of the Middle East during the period 2000-2015 using panel data approach. The results indicated that the underground sector and income inequality had a negative and significant effect on the social development. On the other hand, the increase of government expenditures on the level of health and education had positive and significant effects on the level of social development.